Experimental Investigation of Strengthening Silt With the MICP Technique Combined With Cement - Jiayuan Zhang; Wenbin Lin; Zulei Zhuo; Xiaoqiong Tang; Shanying Wu; Lijin Luo (Advances in Civil Engineering)
In this research, the microbial-induced carbonate precipitation (MICP) technique combined with cement was proposed to improve the physical and mechanical properties of silt. A series of comparative experiments of the MICP technique combined with cement treatments on silt (MICP-reinforced soil-cement) were conducted. The unconfined compressive strength (UCS), internal friction angle, cohesive force, and ultrasonic velocity of the silt treated with the MICP technique combined with cement were higher than those treated with cement. The X-ray diffraction (XRD) and scanning electron microscope (SEM) tests showed that the cement hydration products cemented the silt into agglomerates and formed a skeleton, and the calcite produced by the MICP process covered the surface of the agglomerates and filled the silt pores and cemented the particles, which played a role in increasing the strength of the specimens. In addition, the products and reactants of MICP accelerated the hydration reaction of the cement and played a role in the curing system consistent with carbonate-based and alkaline earth metal–based early-strengthening agents. The results of this study will provide basic theoretical and experimental data for the research and application of microbe-based treatment approaches for silt.